Impact of Government Spending and Corruption on Foreign Direct Investment in Indonesia - Syukri, Adya Utami; Hasanuddin, Basri; Paddu, Abdul Hamid; Suhab, Sultan (Research Papers in Economics and Finance, 2022)
Investment is a critical macroeconomic variable for economic growth and development in any country. As a developing country with the fourth largest population in the world, Indonesia is also dependent on investment coming in from both home and abroad. A good investment climate is one of the solutions in overcoming economic problems so that foreign investors can invest in Indonesia. Obviously, various factors influence investors’ willingness to invest in Indonesia. The purpose of this study is to examine the impact of government spending, corruption, economic growth and wages on foreign direct investment in Indonesia. The study uses Ordinary Least Square (OLS) multiple linear regression analysis for the research period 2000-2020. The results show that the variables of government spending, corruption and economic growth have positive and significant impact on foreign direct investment, while the variable of salary has negative and significant impact on foreign direct investment. The Indonesian government needs to reduce the level of corruption and wage level to attract investors.